Analysis of column cross section towards buckling analysis using civilfem with ansys software - Siti Khadijah, Hubadillah (2013)
This thesis deals with the problem most faced in the design of structures whether building or bridge which called buckling. Buckling is characterized by a sudden failure of a structural member subjected to high compressive stress, where the actual compressive stress at the point of failure is less than the ultimate compressive stresses that the material is capable of withstanding. For example, during earthquakes, reinforced concrete members may experience lateral deformation of the longitudinal reinforcing bars. This mode of failure is also described as failure due to elastic instability. Mathematical analysis of buckling makes use of an axial load eccentricity that introduces a moment, which does not form part of the primary forces to which the member is subjected. When load is constantly being applied on a member, such as column, it will ultimately become large enough to -cause the member to become unstable. Further load will cause significant and somewhat unpredictable deformations, possibly leading to complete loss of load-carrying capacity. The member is said to have buckled, to have deformed. In this research, the structure that going to be analyzed is simple structure of column. The purpose of this research is to observe the effects of how a simple column reacts under loading with different displacement that will be applied. By varying the end supports of a column .will experience different modes of buckling. For the purposes of this project, a buckled column will be defined as a column that displays physical failure. The column is no longer able to support the loading and is forced to deflect laterally. The thesis describes the finite element analysis techniques to illustrate the column buckling modes. Using the ANSYS + CivilFEM Software will show the buckling mode and the stress of the column. Civi1FEM with ANSYS is the most comprehensive and advanced finite element based civil/structural engineering simulation code proven through use. It combines the leading engineering simulation software, ANSYS, and the high-end civil engineering specific structural analysis capabilities of Civi1FEM. In this research, there are steps that need to follow one by one in CiviIFEM with ANSYS Software. This step have been describes in the methodology in this thesis. In this research, there are four condition of displacement or support of the column which are pinned-pinned, fixed-fixed, pinned-fixed, and fixed-free. This research is also proven by the simple formula of column buckling which is Euler Formula. In general, columns do not always terminate with simply-supported ends. Therefore, the formula for the critical buckling load must be generalized.The generalized equation takes the form of Euler's formula, where the effective length of the column Leff depends on the boundary conditions.